2021
DOI: 10.3390/su132111991
|View full text |Cite
|
Sign up to set email alerts
|

Competition in a Household Energy Conservation Game

Abstract: This paper presents the results of a game study, comparing Powersaver Game including a competition feature versus the same game excluding a competition feature with respect to energy conservation in the household. In a pretest–posttest design, we tested whether change in attitude, knowledge and behavior with respect to energy conservation in the household was different for participants playing Powersaver Game with or without competition. All energy conservation activities that the application provides (e.g., w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Kotsopoulos et al (2017) suggested a behavioral research model for workers' energy conservation at work. The empirical impacts of some serious play in altering knowledge, behavior, and attitude towards energy conservation have been beneficial (Fijnheer et al, 2016). User behavior is influenced by a variety of elements, including monetary considerations, moral principles, and everyday routines.…”
Section: Energy Consumptionmentioning
confidence: 99%
“…Kotsopoulos et al (2017) suggested a behavioral research model for workers' energy conservation at work. The empirical impacts of some serious play in altering knowledge, behavior, and attitude towards energy conservation have been beneficial (Fijnheer et al, 2016). User behavior is influenced by a variety of elements, including monetary considerations, moral principles, and everyday routines.…”
Section: Energy Consumptionmentioning
confidence: 99%
“…However, we have also found that there were some gaming elements and persuasive mechanisms which were not adopted at all; researchers could therefore pay more attention to these neglected elements and mechanisms. In addition, despite the variance of the gaming mechanisms and the persuasive mechanisms deployed, we have noticed that only a small portion (14%) of the reviewed articles had a straightforward focus on evaluating the design of the deployed BCGs, seeking to identify the most effective gaming elements and persuasive strategies for empowering players' EC (see for example [38,67,69,78]). This finding echoes Hammady's and Arnab's remark that "existing studies and reviews often report the effectiveness of game interventions on behavior change without offering any insights into why and how games and gameplay are effective on a granular design level by reflecting on the choice of game elements used in the design" [4] (p. 3).…”
Section: Gaming Elements and Persuasive Mechasnismsmentioning
confidence: 99%
“…Prior work has attempted to make invisible consumption visible through technologies such as web-based apps/mobile applications [6,65], games [41], virtual environments [25], and data sculptures [91,95]. However, most prior work on designing technologies for domestic consumption has not explored how household practices inform the design [95].…”
Section: Existing Challenges In Encouraging Sustainable Practices In ...mentioning
confidence: 99%